Toward A Dynamic and Automated IP Environment - Abdulrahman Abdulbaki, Mohammed Saad Al-Qahtani (International Journal of Advanced Science and Technology, 2020)
The growth and complexity of data center networks in the context of virtualization, high performance, supercomputing and cloud computing services has led to an enormous demand for dynamic and automated IP address environment.  Apart from the conventional challenges in business continuity, reliability, security, scalability and management flexibility, the need for a modern dynamic IP Address Management (IPAM) environment has become more pronounced in large-scale energy-sector data centers, foreseeing the exponential growth of IP devices combined with the complexity introduced by IT services (e.g. VoIP, Cloud computing, Server and Desktop Virtualization). Traditional methods of managing IP addresses manually with spreadsheets and static IP assignment cannot keep pace with the growing demands of virtualization and automation. This paper explains a novel design approach suitable for heterogeneous large-scale data centers, aiming to make corporate IPAM services run simpler, more efficient, and secure while utilizing automation as a core building block for corporate network IP services.